Working conditions in nursing in the face of Covid-19 from the perspective of precariousness - Ana Paula Nogueira de Magalhães; Diego de Oliveira Souza; Fernanda Pereira de Macêdo; Sabrina Ângela França da Silva Cruz; Camila Pereira-Abagaro; Roselia Arminda Rosales-Flores (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To investigate working conditions in nursing when facing the Covid-19 pandemic, in light of aspects of precarious work. Methods: Cross-sectional study, with 131 nursing workers who worked against Covid-19 in hospitals in Alagoas State, Northeast Brazil. Data were collected online, using a workers' health assessment questionnaire. The Chi -Square or Fisher's Exact test and logistic regression were used. Results: among nursing workers, 71% had precarious contracts, 33.6% reported extended working hours and 23.7% were union members. In the multivariable analysis, having little hospital experience was a predictor for poor employment (OR= 2.408; 95%CI= 1.051-5.518). The predictor variables for lengthening the working day were being a nurse (OR= 3.824; 95%CI= 1.274-11.483); overtime (OR= 3.668; 95%CI= 1.009-13.333) and inadequate number of workers (OR= 10.872; 95%CI= 3.409-34.675). Being a nursing technician was a predictor of being a union member (OR= 8.967; 95%CI=2.560-31.410). Conclusions: The pandemic has accentuated the precariousness of working conditions in nursing professionals, especially among nurses.